Cost-Efficient Digital Elevation Model (DEM) Acquisition on Flume Tank Morphodynamic Observation - Prasojo, Octria Adi; Aufar, Adlirrahman; Syahputra, Reza (UIR PRESS, 2024)
Digital Elevation Model (DEM) is well known for providing solutions to the theoretical and application-related problems around geosciences. The use of DEM in flume tank experiment is getting more common nowadays. Flume tank itself is built to simulate the landscape and stratigraphy at laboratory scale. This physical experiment may have tremendous impacts on understanding the sedimentation process in a laboratory-scaled experiment. Normally, the morphodynamic behaviour of a laboratory-scaled deposit in the flume tank experiment would be observed through its digital elevation model. In this paper, a novel method in constructing cost-efficient digital elevation model was presented. By using this inexpensive tool to create a digital elevation model in a flume tank experiment setup, some challenges and benefits will follow this method. Some challenges including tool’s resolution and time consuming could be diminished in the near future by creating automated motor system to move the laser distance meter sequentially. Automated and integrated system from the LDM to the processing software could also reduce the time consumption. In the other hand, some benefits including financial benefit, reliability in a sedimentary structure scale, and also the practicality to be applied in any flume tank system available in Indonesia. Nevertheless, this method had been tested and some reliable results from the previous studies in Quantitative Sedimentology Laboratory, Universitas Indonesia was presented in this paper. Hopefully, some major improvements could be done to get more accurate and detail digital elevation model in the near future.